Perancangan Sistem Informasi Helpdesk Menggunakan Framework ITIL V3 - Evasaria M. Sipayung; Cut Fiarni; Ernest Aditya (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
In order to improve and to ensure the availability of information technology (IT) services quality, many organizations now have a helpdesk which acts as a center point in solving and organizing problems. However, in the planning and implementation of Information Systems Service Helpdesk, it is necessary to do a thorough analysis of the framework of the Information Technology Service Management (ITSM) that is appropriate and in accordance with the needs of organizations, that is also capable of providing the function of knowledge management. It is because each type of organization has different needs and Standard Operation Procedure in providing IT services. The purpose of this study is to analyze the right ITSM framework in developing Helpdesk Information System in PT Len Industri (Persero), which is one of State-Owned Enterprises (SOEs). Helpdesk services provide repairs of hardware, software, and network. Previously, informations about problems and the handling are not complete, and the information storing is unstructured. This causes difficulties in monitoring and evaluation activities conducted by helpdesk admin and manager of Information Systems. To solve this problem, a system is designed using ITSM best practices standard from the Information Technology Infrastructure Library version 3. The system is designed to perform the classification to every problem. Classifications are made into several level of priorities which correspond with profile matching method, according to position and division within the PT Len Industri (Persero)’s value chain. The developed dashboard has been able to support the helpdesk results evaluation process. To ensure the usability of the system, a user acceptance test is conducted with the standard of Unified Theory of Acceptance and Use of Technology. The system obtains overall score of 88,89% in the user interface aspect and 83,715% in the functional requirement of information system aspect.